TANGGUNGJAWAB PT POS INDONESIA (PERSERO) ATAS KETERLAMBATAN SAMPAINYA PAKET POS KIRIMAN PENGIRIM DI KOTA PONTIANAK - NIM. A1011171092, AMELLIA DINI SEFITIOLA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The agreement for sending postal packages or goods made between PT. Pos Indonesia (Persero) with the sending party creates a legal relationship which strictly regulates the rights and obligations of both parties. PT. Pos Indonesia (Persero) has the obligation to deliver the postal parcel belonging to the sender at the specified time. The rights of the PT. Pos Indonesia (Persero) is to get payment for the services he has done. The sender has the right to get the best service from PT. Pos Indonesia (Persero), namely the postal package belonging to the sender is sent and arrives at the specified time, and its obligation is to pay for the transportation service (shipping fee) to the party that sent it, namely PT. Pos Indonesia (Persero). The formulation of the problem in this study is :